Risk and Damage Analysis of Nile Tilapia (Oreochromis niloticus) Commodities During The Shipping Process at Selili Fishing Port, Samarinda, Indonesia: English - Pratama, Andri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Tilapia is a freshwater fish commodity widely preferred by consumers in Samarinda. Due to high market demand, fish farmers have to increase the number of tilapia shipments to meet it. The Selili Fishing Port (PPI Selili) is a port where tilapia farmers can market their fish to consumers on a large scale. Transporting tilapia in open vehicles and exceeding their load capacity can cause damage to tilapia products. This study aimed to identify the sources of hazards and risks associated with the use of open vehicles for tilapia transport. Data were collected through direct observation and interviews and analyzed using Hierarchical Task Analysis (HTA), Hazard Identification and Risk Assessment (HIRA), organoleptic testing of Nile tilapia quality, and descriptive analysis. The results of this study showed that there are three stages in the tilapia shipping process: the loading stage, with six potential hazards; the transportation stage, with three potential risks; and the unloading stage, with five potential hazards that can reduce tilapia quality. Organoleptic testing showed that the tilapia remained acceptable and fit for consumption, with the highest score of 8.00 recorded during loading and the lowest during unloading, 7.00. This study provides information on the sources of hazards and risk levels in the activity of transporting tilapia in open vehicles, presented in HTA and HIRA tables.